2020
DOI: 10.1186/s13052-020-0773-0
|View full text |Cite
|
Sign up to set email alerts
|

Survey of PDA management in very low birth weight infants across Italy

Abstract: Background: The optimal management of PDA in very low birth weight (VLBW) infants is still controversial. Aim of our study was to investigate the management of PDA in the Italian neonatal intensive care units (NICU). Methods: We conducted an on-line survey study from June to September 2017. A 50-items questionnaire was developed by the Italian Neonatal Cardiology Study Group and was sent to Italian NICUs. Results: The overall response rate was 72%. Diagnosis of PDA was done by neonatologists, cardiologists or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 42 publications
1
7
0
Order By: Relevance
“…Four authors (I. C., B. F., M. S., N. P.) developed a 33-item questionnaire according to the Checklist for Reporting Results of Internet E-Surveys (CHERRIES) 22 and a previously published survey. 23 The questionnaire was divided into eight sections: epidemiological and organizational characteristics of the center; medical staff assigned to conduct LU; ultrasound equipment for LU; imaging storage and reporting; infection control, cardiorespiratory and thermal stability; practice of LU as "descriptive" tool; practice of LU as "functional" tool; training needs. Survey Monkey was used as an online survey platform.…”
Section: Questionnairementioning
confidence: 99%
“…Four authors (I. C., B. F., M. S., N. P.) developed a 33-item questionnaire according to the Checklist for Reporting Results of Internet E-Surveys (CHERRIES) 22 and a previously published survey. 23 The questionnaire was divided into eight sections: epidemiological and organizational characteristics of the center; medical staff assigned to conduct LU; ultrasound equipment for LU; imaging storage and reporting; infection control, cardiorespiratory and thermal stability; practice of LU as "descriptive" tool; practice of LU as "functional" tool; training needs. Survey Monkey was used as an online survey platform.…”
Section: Questionnairementioning
confidence: 99%
“…Current opinions vary widely on when and how to detect J o u r n a l P r e -p r o o f 6 PDA, and whether and how to treat it. [1][2][3] Many previous studies reported variable results on the effectiveness of PDA treatment to improve the outcomes of very preterm infants. Most previous studies studied the treatment of symptomatic PDA.…”
Section: Discussionmentioning
confidence: 99%
“…The following echocardiographic measurements were carried out as previously described: shortening fraction (SF), ejection fraction (EF) [ 18 , 22 ], mitral valve Doppler E wave, A wave and E/A ratio, Tissue Doppler Imaging e’, a’, s’; E/e’ ratio [ 23 ], left ventricular output [ 24 ], PDA diameter, PDA maximum velocity, left pulmonary artery (LPA) diastolic velocity and reverse diastolic flow in descending aorta [ 25 ]. A PDA was defined as hemodynamically significant (hsPDA) if the following conditions were fulfilled at 48 h: (1) PDA diameter was > 1.5 mm; (2) maximum velocity of flow across PDA was < 2 m/s; (3) LPA diastolic velocity was > 0.2 m/s; (4) LVO was > 200 mL/kg/min and (5) there was evidence of reverse diastolic flow in descending aorta [ 25 , 26 ].…”
Section: Methodsmentioning
confidence: 99%